China and the South China Sea: What Happened to ASEAN’s Solidarity? - Roberts, Christopher (2016)
ON 14 March this year, Vietnam, the Philippines and China announced an agreement to conduct joint exploration within certain parts of the South China Sea. This announcement has had the effect of isolating the remaining ASEAN claimants Malaysia, Brunei and Indonesia - while raising the potential for ASEAN disunity. In addition, recent displays of discord – such as the tensions between Indonesia and Malaysia over the Sulawesi Sea – have the added risk of emboldening Beijing to be more assertive in its relations with ASEAN. It is only through greater unity that ASEAN will continue to exercise sufficient leverage to ensure that its relationship with China remains as economically and politically beneficial as possible.